A Brazilian multicentre study evaluating pregnancies induced by cabergoline in patients harboring prolactinomas - Sant’ Anna, B. G.; Musolino, N. R.C.; Gadelha, M. R.; Marques, C.; Castro, M.; Elias, P. C.L.; Vilar, L.; Lyra, R.; Martins, M. R.A.; Quidute, A. R.P.; Abucham, J.; Nazato, D.; et al. (Springer Nature, 2020)
Objective: To evaluate the maternal–fetal outcomes of CAB-induced pregnancies in patients with prolactinoma in a large cohort. Methods: The prevalence of tumor growth, miscarriage, preterm, low birth weight, congenital malformations and impairment in neuropsychological development in children among women treated with CAB were assessed in a Brazilian multicentre retrospective observational study, Results: We included 194 women with a mean age of 31 (17–45) years, 43.6% presenting microadenomas and 56.4% macroadenomas, at prolactinoma diagnosis. In 233 pregnancies, CAB was withdrawn in 89%, after pregnancy confirmation. Symptoms related to tumor growth occurred in 25 cases, more frequently in macroadenomas. The overall miscarriage rate was 11%, although higher in the subgroup of patients with CAB maintainance after pregnancy confirmation (38% vs. 7.5%). Amongst the live-birth deliveries, preterm occurred in 12%, low birth weight in 6% and congenital malformations in 4.3%. Neuropsychological development impairment was reported in 7% of cases. Conclusions: Our findings confirm previous results of safety in maternal and fetal outcomes in CAB-induced pregnancies; nevertheless, CAB maintenance after pregnancy confirmation was associated with higher miscarriage rate; result that must be further confirmed.
Keywords: Cabergoline; Dopamine agonist; Malformation; Miscarriage; Pregnancy; Prolactinoma